Emotional AI : the rise of empathic media - McStay, Andrew 1975- (Los Angeles : SAGE, 2018)
What happens when media technologies are able to interpret our feelings, emotions, moods, and intentions? In this cutting edge new book, Andrew McStay explores that very question and argues that these abilities result in a form of technological empathy. Offering a balanced and incisive overview of the issues raised by 'Emotional AI', this book: Provides a clear account of the social benefits and drawbacks of new media trends and technologies such as emoji, wearables and chat bots, Demonstrates through empirical research how 'empathic media' have been developed and introduced both by start-ups and global tech corporations such as Facebook, Helps readers understand the potential implications on everyday life and social relations through examples such as video-gaming, facial coding, virtual reality and cities, Calls for a more critical approach to the roll out of emotional AI in public and private spheres. Combining established theory with original analysis, this book will change the way students view, use and interact with new technologies. It should be required reading for students and researchers in media, communications, the social sciences and beyond.
Keywords: INTELIGENCIA ARTIFICIAL -- ASPECTOS SOCIALES; EMPATÍA -- SIMULACIÓN POR COMPUTADORA; COMUNICACION -- INNOVACIONES TECNOLOGICAS; MEDIOS DE COMUNICACION DE MASAS -- INNOVACIONES TECNOLOGICAS